2022
DOI: 10.3390/electronics11091354
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Re-Identification with Spatio-Temporal Model Leveraging by Pose View Embedding

Abstract: Vehicle re-identification (Re-ID) research has intensified as numerous advancements have been made along with the rapid development of person Re-ID. In this paper, we tackle the vehicle Re-ID problem in open scenarios. This research differs from the early-stage studies that focused on a certain view, and it faces more challenges due to view variations, illumination changes, occlusions, etc. Inspired by the research of person Re-ID, we propose leveraging pose view to enhance the discrimination performance of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Liu et al [12] proposed "PROVID" and made progress with the use of license plate information. Other studies [13,14] have shown that spatial and temporal information from vehicle images have contributed to improving vehicle re-ID performance. For example, PROVID [12] re-ranks vehicles using spatio-temporal properties based on a simple from-near-distant principle.…”
Section: Vehicle Re-id Methodsmentioning
confidence: 99%
“…Liu et al [12] proposed "PROVID" and made progress with the use of license plate information. Other studies [13,14] have shown that spatial and temporal information from vehicle images have contributed to improving vehicle re-ID performance. For example, PROVID [12] re-ranks vehicles using spatio-temporal properties based on a simple from-near-distant principle.…”
Section: Vehicle Re-id Methodsmentioning
confidence: 99%
“…Method Type Advantage Limitation [19,20] Deep learning High recognition accuracy High cost; poor interpretability [21,22] Spatiotemporal information Works well for hard samples Additional complex spatiotemporal labels are required [16,17] Metrics learning High recognition accuracy High cost [23,24] Multidimensional information based…”
Section: Referencementioning
confidence: 99%